Longitudinal optic neuritis-unrelated visual evoked potential changes in NMO spectrum disorders. (28th January 2020) - Ringelstein, Marius; Harmel, Jens; Zimmermann, Hanna; Brandt, Alexander U.; Paul, Friedemann; Haarmann, Axel; Buttmann, Mathias; Hümmert, Martin W.; Trebst, Corinna; Schroeder, Christoph; Ayzenberg, Ilya; Kleiter, Ingo; et al.
Abstract : Objective: To investigate if patients with neuromyelitis optica spectrum disorder (NMOSD) develop subclinical visual pathway impairment independent of acute attacks. Methods: A total of 548 longitudinally assessed full-field visual evoked potentials (VEP) of 167 patients with NMOSD from 16 centers were retrospectively evaluated for changes of P100 latencies and P100-N140 amplitudes. Rates of change in latencies (RCL) and amplitudes (RCA) over time were analyzed for each individual eye using linear regression and compared using generalized estimating equation models. Results: The rates of change in the absence of optic neuritis (ON) for minimal VEP intervals of ≥3 months between baseline and last follow-up were +1.951 ms/y (n = 101 eyes; SD = 6.274; p = 0.012) for the P100 latencies and −2.149 µV/y (n = 64 eyes; SD = 5.013; p = 0.005) for the P100-N140 amplitudes. For minimal VEP intervals of ≥12 months, the RCL was +1.768 ms/y (n = 59 eyes; SD = 4.558; p = 0.024) and the RCA was −0.527 µV/y (n = 44 eyes; SD = 2.123; p = 0.111). The history of a previous ON >6 months before baseline VEP had no influence on RCL and RCA. ONs during the observational period led to mean RCL and RCA of +11.689 ms/y (n = 16 eyes; SD = 17.593; p = 0.003) and −1.238 µV/y (n = 11 eyes; SD = 3.708; p = 0.308), respectively. Conclusion: This first longitudinal VEP study of patients with NMOSD provides evidence of progressive VEP latency delay occurring independently of acute ON. Prospective longitudinal studies are needed to corroborate these findings and help to interpret the clinical relevance.